More Thumbs Than Rules: Is Rationality an Exaptation? - Mastrogiorgio, Antonio; Felin, Teppo; Kauffman, Stuart; Mastrogiorgio, Mariano (Frontiers in Psychology, 2022)
In this contribution, we argue that adaptive mechanisms are not sufficient for explaining human rationality, and we posit that human rationality presents exaptive origins, where exaptations are traits evolved for other functions or no function at all, and later co-opted for new uses. We propose an embodied reconceptualization of rationality—embodied rationality—based on the reuse of the perception-action system, where many neural processes involved in the control of the sensory-motor system, salient in ancestral environments, have been later co-opted to create—by tinkering—high-level reasoning processes, employed in civilized niches.